Dual-target one-step nested PCR for sensitive detection of SARS-CoV-2 nucleic acids. Issue 4 (1st April 2022) - Li, Qijie; Xia, Yiqing; Liao, Dunshui; Nie, Hu; Zhang, Ming; Wang, Tinghua; Liao, Jiayu; Xia, Qingjie
Abstract: The Corona Virus Disease reported in 2019 (COVID-19) poses a significant threat to human and public health. Its early and accurate detection can reduce the spread and recurrence of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Real-time reverse transcription fluorescent quantitative polymerase chain reaction (RT-qPCR) is the "gold standard" for detecting the nucleic acid of SARS-CoV-2. This study developed and tested a dual-target (ORF1ab and N gene) one-step nested RT-qPCR (DTO-N-PCR) to detect SARS-CoV-2. Ten-fold serial dilutions of mixed synthetic DNA from SARS-CoV-2 ORF1ab and N gene were used as templates to test the sensitivity of DTO-N-PCR. Its specificity was subsequently tested using throat swab specimens from 10 COVID-19 patients and 35 healthy participants. DTO-N-PCR was more sensitive and specific than conventional RT-qPCR. It has unique features, including a dual-target (ORF1ab and N gene), rapid one-step operation of reverse transcription and PCR, four pairs of inner and outer primers, and specific probes. These features aid in its rapid, accurate, and efficient detection of SARS-CoV-2 RNA.